An investigation into the mechanism and function of cysteine oxidation in the plant N-end rule pathway - Rooney, D.J. (2017)
Flooding events are becoming more common throughout the world as a result of climate change, resulting in reduced crop yields. It was recently discovered that plants sense low oxygen (O2) (associated with flooding) through regulated proteolysis of the group VII Ethylene Response Factor transcription factors (ERFVIIs), via the Cys-Arg/N-end rule pathway of ubiquitin mediated proteolysis, which also senses another gas, nitric oxide (NO). The N-terminal (Nt) Cys of physiological (e.g. ERFVIIs) and artificial substrates was shown to be key for N-end rule function, and work in mammalian systems suggested that oxidation of Nt-Cys by O2 and NO was a required prerequisite for subsequent Nt arginylation by arginyl tRNA transferases (ATEs). However the exact mechanism of Nt-Cys oxidation has not been discovered. The primary aim of this thesis was to define the mechanism of in vivo Nt-Cys oxidation essential in determining the stability of Arg/N-end rule protein substrates, including ERFVIIs. In this study a novel approach was developed to investigate the oxidation of Nt-Cys in vivo using transgenic Arabidopsis expressing Cys-2 reporter proteins (derived from the transgenes 35S::MC-polyG-HA-GUS and Ubi1::MCGGAIL-GUS). Cys-2 of the reporter proteins is made Nt constitutively by co-translational Methionine Aminopeptidase (MAP) activity. Biochemical techniques were combined with analytical chemistry to investigate the in vivo oxidation of Nt-Cys using liquid chromatography mass spectrometry (LC-MS). In addition, synthetic peptides representing the Nt-sequence of the in vivoreporter protein were used to define the oxidative and nitrosylative modifications occurring at Nt-Cys in vitro. Findings of this study include the successful development of two new in vivo O2 sensor artificial N-end rule substrates, in the plant genetic model Arabidopsis thaliana. A further outcome revealed that the ERFVII RELATED TO APETALA 2.12 (RAP2.12) is stabilised in the shoot and root apical meristem to a greater extent than in other regions of seedlings in response to hypoxia, indicating that meristematic cells could be important oxygen sensory zones. Cys-2 reporter proteins were used in in vivo studies to attempt to identify the nature of the Nt residues following N-end rule action. Although Nt-peptides derived from affinity purified Cys-2 reporter protein were not identified by LC-MS, it was possible to demonstrate that ubiquitination is required on Cys-2 reporter proteins before 26S proteasome degradation. Combined results from Nt-Cys in vitro synthetic peptides and Cys-2 reporter proteins substrates of the Arg/N-end rule pathway, provide indirect evidence that post translational modifications (PTMs)not defined before occur in vivo. Using synthetic peptides it was possible to show evidence for Nt-Cys-sulfenamide formation after oxidation of Nt-Cys. This finding suggests that Cys-sulfenamide formation, a previously recognised reversible modification preventing irreversible oxidation to Cys-sulfonic acid, could occur at Nt-Cys of in vivoprotein substrates. An important finding of this study was the observednonreactionbetween the nitrosylated Nt-Cys and H2O or conversely oxidised Nt-Cys and NO. As Plant Cysteine Oxidases (PCOs) do not require NO to oxidise Nt-Cys, this result raises further uncertainty as to how NO is involved in the oxidation of Nt-Cys, suggesting that NO may be involved in the enzymatic activation of PCOs or the arginylation of Nt-Cys by ATEs. The findings of this study did not identify the Nt-peptide of the Cys-2 reporter protein, and hence the Nt-Cys oxidation state of an in vivo substrate of the Arg/N-end rule pathway remains unidentified. Despite this the result that Nt-Cys can be oxidised to Cys-sulfenamide is novel and an important discovery to the field of reactive Cys biology and chemistry.